Formation of Successful Personality in the Vision of Outstanding Contemporaries: Array - Bashtovenko , Oksana (Journal of Danubian Studies and Research, 2021)
The article is devoted to the disclosure of the positions and considerations of prominent contemporaries who are world leaders in business, education, journalism, and politics. We analyze the speeches in which they speak about their position, give advice for university graduates. The analysis of the speeches provided an opportunity to identify the global problems of humanity and listen to personal recommendations regarding the crisis in society. What is success, how to achieve it? What are the main obstacles and important points on the way to achieving success? Can the success of one person be considered a priority and the main criterion of life? What do outstanding personalities consider an important moment for their lives, what prospects do they predict for all of humanity? There are answers to such important questions. These answers are found in the global pillars of liberal arts education - critical thinking and humanity.